Gender response in laboratory activity based on creative research project on biology creative thinking skills of high school students - AA. Sukarso; Ari Widodo; Diana Rochintaniawati; Widi Purwianingsih (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The study of creative thinking skills has focused on creative research project-based laboratory activity for high school students' biology learning. The purpose of this study is to explore the differences in the creative thinking ability of male and female students. The participants of this study were students of X MIPA consisting of 22 males and 37 females students in a high school of Mataram, Lombok, NTB. Students completed a biological creative thinking skills test after completing a laboratory learning activity based on creative research project that was required to be encouraged by activities and creative thinking. The results showed that there was evidence of an improvement trend of creative thinking skills in all male and female students. However, statistical analysis using independent sample t-test showed no significant difference to the mean scores obtained by male and female students. The results of the study are discussed based on the existing literature on developmental trends and gender differences in creative thinking.